Contact Effect of a Methylobacterium sp. Extract on Biofilm of a Mycobacterium chimaera Strain Isolated from a 3T Heater-Cooler System - Inés Pradal; Jaime Esteban; Arancha Mediero; Marta García-Coca; John Jairo Aguilera-Correa (MDPI AG, 2020)
Mycobacterium chimaera is an opportunistic slowly growing non-tuberculous mycobacteriumof increasing importance due to the outbreak of cases associated with contaminated 3T heater-cooler device (HCD) extracorporeal membrane oxygenator (ECMO). The aim of this study was to evaluate the effect of pre-treating a surface with a Methylobacterium sp. CECT 7180 extract to inhibit the M. chimaera ECMO biofilm as well as of the treatment after different dehydration times. Surface adherence, biofilm formation and treatment effect were evaluated by estimating colony-forming units (CFU) per square centimeter and characterizing the amount of covered surface area, thickness, cell viability, and presence of intrinsic autofluorescence at different times using confocal laser scanning microscopy and image analysis. We found that exposing a surface to the Methylobacterium sp. CECT 7180 extract inhibited M. chimaera ECMO biofilm development. This effect could be result of the effect of Methylobacterium proteins, such as DNaK, trigger factor, and xanthine oxidase. In conclusion, exposing a surface to the Methylobacteriumsp. extract inhibits M. chimaera ECMO biofilm development. Furthermore, this extract could be used as a pre-treatment prior to disinfection protocols for equipment contaminated with mycobacteria after dehydration for at least 96 h.